Public Relations as Managerial Function in University Management - Setyanto, Yugih; Dida, Susanne; Novianti, Evi (Jurnal Komunikasi, 2025)
Public Relations (PR) has a strategic role as a managerial function in university management to support the achievement of the vision and mission of higher education institutions. This article examines the position, function, and strategy of PR within the university organizational structure, as well as its role in facilitating two-way communication between the organization and the public. Using theoretical and practical approaches, the article highlights the importance of PR in building harmonious relationships, managing the institution's image, and communicating strategic policies. In addition, it discusses the challenges faced by PR in universities, such as the low attention of the leadership to the role of PR and the need to develop the competence of the PR team. Placing PR in a strategic structural position can improve communication effectiveness, strengthen relationships with internal and external publics, and support the implementation of the Tri Dharma of Higher Education. This article emphasizes that PR is a managerial function that has a strategic role in supporting the success of university management. PR does not only carry out communication tasks, but is also involved in building an image, maintaining mutually beneficial relationships between the university and its public, and supporting the achievement of the institution's vision and mission.